2022
DOI: 10.1002/adma.202205309
|View full text |Cite
|
Sign up to set email alerts
|

Hot‐Casting‐Assisted Liquid Additive Engineering for Efficient and Stable Perovskite Solar Cells

Abstract: High‐performance inorganic–organic lead halide perovskite solar cells (PSCs) are often fabricated with a liquid additive such as dimethyl sulfoxide (DMSO), which retards crystallization and reduces roughness and pinholes in the perovskite layers. However, DMSO can be trapped during perovskite film formation and induce voids and undesired reaction byproducts upon later processing steps. Here, it is shown that the amount of residual DMSO can be reduced in as‐spin‐coated films significantly through use of preheat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 61 publications
0
34
0
Order By: Relevance
“…The presence of PbO (which does not dissolve well) caused nearly complete degradation (96%), which is also consistent with the fact that PbO can react with 3 equivalents of MAI to make MAPbI 3 and H 2 O, releasing 2 equivalents of methyl­amine. It is most notable that water has such a small effect on the MFA reaction, given a recent report, yet logical since DMSO more readily accepts a proton than H 2 O in these aprotic solvent environments. …”
mentioning
confidence: 99%
“…The presence of PbO (which does not dissolve well) caused nearly complete degradation (96%), which is also consistent with the fact that PbO can react with 3 equivalents of MAI to make MAPbI 3 and H 2 O, releasing 2 equivalents of methyl­amine. It is most notable that water has such a small effect on the MFA reaction, given a recent report, yet logical since DMSO more readily accepts a proton than H 2 O in these aprotic solvent environments. …”
mentioning
confidence: 99%
“…19 In addition, Rand et al spontaneously employed substrate per-heated treatment and solvent regulation to reduce the adducts and intermediate species in precursor films, thus suppressing the formation of byproducts and reducing solvate residual. 18,20 modulation of precursor components is also a widely used approach to produce the high-pure perovskite phase. Zhang et al found that cesium cations required relatively lower energy to diffuse into IP frameworks compared with DMSO, thus promoting the release of solvent molecules; consequently, a well-crystallized cesium-doped perovskite film without any impurity phases was obtained at near room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, the in the film will produce some by-products that will affect the perovskite phase purity and device performance. [18,19] It is revealed that the 2D perovskite films suffer from more severe defects than 3D films, [20] and the surface trap density is twoorder higher than that of bulk materials. [21] So most researchers have focused on surface passivation to improve the efficiency of 2D PSCs.…”
Section: Introductionmentioning
confidence: 99%